Expression of dehydrins in wheat and barley under different temperatures - Kosová, Klára; Vítámvás, Pavel; Prášil, Ilja Tom (Plant science, 2011)
The review summarizes recent knowledge on the expression of cold-inducible dehydrins with a special attention to Wcs120 and Dhn5 genes in wheat and barley plants under different temperatures. When plants are exposed to cold, dehydrins start accumulating both in freezing-tolerant and freezing-susceptible plants; however, their accumulation correlates with plant acquired frost tolerance (FT). During a long-term cold acclimation (CA), dehydrin accumulation is significantly affected by Vrn1/Fr1 locus and the expression of the major vernalization gene VRN1, respectively. A different dynamics of dehydrin transcripts and proteins during CA is also observed. Transcripts reach their maximum within the first week of CA while proteins gradually accumulate until vernalization. Vernalization is associated with a significant decrease in dehydrin accumulation while the decrease of acquired FT is delayed. Studies carried out on plants grown at moderately cold temperatures (9-20 °C) have shown that both dehydrin transcripts and proteins can be detected even at these temperatures and that plants with different FT levels can be distinguished according to dehydrin accumulation without any exposure to severe cold. In conclusion, the potential use of these results in the breeding programmes aimed at the enhancement of wheat and barley FT is discussed.
Keywords: Plant Proteins; Triticum; ječmen (rod); pšenice; Hordeum; rostlinné proteiny; regulace genové exprese u rostlin; Gene Expression Regulation, Plant